2017
DOI: 10.1371/journal.pone.0172894
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen uptake efficiency slope as a useful measure of cardiorespiratory fitness in morbidly obese women

Abstract: Cardiopulmonary assessment through oxygen uptake efficiency slope (OUES) data has shown encouraging results, revealing that we can obtain important clinical information about functional status. Until now, the use of OUES has not been established as a measure of cardiorespiratory capacity in an obese adult population, only in cardiac and pulmonary diseases or pediatric patients. The aim of this study was to characterize submaximal and maximal levels of OUES in a sample of morbidly obese women and analyze its re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…OUES was higher in men suggesting a better O 2 delivery and extraction of oxygen during exercise. Baseline OUES correlated positively with VO 2MAX [18, 48] in women and men. Our data showed that baseline OUES correlated significantly with VO 2MAX being the correlation coefficient higher in women.…”
Section: Discussionmentioning
confidence: 99%
“…OUES was higher in men suggesting a better O 2 delivery and extraction of oxygen during exercise. Baseline OUES correlated positively with VO 2MAX [18, 48] in women and men. Our data showed that baseline OUES correlated significantly with VO 2MAX being the correlation coefficient higher in women.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen uptake efficiency slope (OUES), as a submaximal measure of cardiorespiratory functional reserve, is derived from the relation between oxygen uptake (V o 2 , mL/min) and minute ventilation (V e , liters/min) during incremental exercise and is determined by V o 2 = a log V e + b, where a = OUES, which shows the effectiveness of V o 2 [ 30 ]. Determination of the efficiency of oxygen uptake in overweight persons is already a golden standard of modern physiology [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. It is an indicator determining an organism’s oxygen consumption under dynamic conditions of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…In common with the measurement of AT, one benefit of the OUES is that it can be obtained from a submaximal test, and so it is not as dependent on patient volition as a V O 2 measurement. It may also be useful in patients who are unable to perform a maximal exercise test as may be the case in morbid obesity [41] and those with poor mobility or joint problems. It is therefore possible to obtain useful data for the vast majority of patients.…”
Section: Oxygen Uptake Efficiency Slopementioning
confidence: 99%